Peran Bank dalam Pelindungan Ekonomi terhadap Pekerja Migran Indonesia (The Role of Bank in Economic Protection for Indonesian Migrant Workers) - Dian Cahyaningrum (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2020)
Indonesian migrant workers often go through cases, and therefore need protection, including economic protection. This paper reviews and aims to determine the importance of economic protection for Indonesian migrant workers and the role of banks in economic protection. This study has theoretical and practical uses. It was conducted using normative and empirical juridical methods in Indramayu and Wonosobo Districts. Under the Law on Protection of Indonesian Migrant Workers, economic protection for migrant workers is provided through remittance management, as well as financial and entrepreneurship education. Unfortunately the government regulation on economic protection for migrant workers has not yet been formed. There are some importance of economic protection for migrant workers, namely: better management of remittances, increased literacy and financial inclusion of the migrant workers, more businesses owned by migrant workers, and reduced unemployment. Banks have some important roles in supporting economic protection for Indonesian migrant workers, including: providing financial education and money transfer services, implementing CSR, and channeling business credit. However, there are obstacles faced by banks in carrying out their roles, namely the education house is less functioning when there is no mover and many cooperatives are not well managed. In order for economic protection to work well, it is recommended that the government regulation on economic protection for migrant workers be immediately formed; pre-departure financial education is carried out; role of assistance team on productive migrant villages actively played; and cooperatives must be well managed. AbstrakPekerja Migran Indonesia (PMI) seringkali tertimpa kasus, oleh karenanya perlu mendapat pelindungan, termasuk pelindungan ekonomi. Tulisan ini mengkaji dan bertujuan untuk mengetahui pentingnya pelindungan ekonomi terhadap PMI dan peran bank dalam pelindungan ekonomi tersebut. Tulisan memiliki kegunaan teoritis dan praktis. Penelitian dilakukan dengan menggunakan metode yuridis normatif dan empiris di Kabupaten Indramayu dan Kabupaten Wonosobo. Berdasarkan UU PPMI, pelindungan ekonomi terhadap PMI dilakukan melalui pengelolaan remitansi, pemberian edukasi keuangan dan kewirausahaan kepada PMI. Sayangnya peraturan pemerintah (PP) pelindungan ekonomi terhadap PMI belum terbentuk. Pentingnya pelindungan ekonomi bagi PMI antara lain: remitansi PMI dapat dikelola dengan baik, literasi dan inklusi keuangan PMI meningkat, PMI memiliki usaha, dan mengurangi pengangguran. Bank memiliki peran penting dalam mendukung pelindungan ekonomi terhadap PMI, diantaranya: memberikan edukasi keuangan dan layanan pengiriman uang, melaksanakan CSR, dan menyalurkan KUR. Namun ada kendala yang dihadapi bank dalam melaksanakan perannya, yaitu rumah edukasi kurang berfungsi jika tidak ada penggeraknya dan banyak koperasi yang tidak dikelola dengan baik. Agar pelindungan ekonomi berjalan dengan baik disarankan PP pelindungan ekonomi terhadap PMI segera dibentuk; edukasi keuangan dilakukan sebelum PMI berangkat ke luar negeri, pendamping desmigratif harus berperan aktif; dan koperasi harus dikelola dengan baik.